2020
DOI: 10.1126/sciadv.aay6193
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of vegetation and climate variability on the Tibetan Plateau over the past 1.74 million years

Abstract: The Tibetan Plateau exerts a major influence on Asian climate, but its long-term environmental history remains largely unknown. We present a detailed record of vegetation and climate changes over the past 1.74 million years in a lake sediment core from the Zoige Basin, eastern Tibetan Plateau. Results show three intervals with different orbital- and millennial-scale features superimposed on a stepwise long-term cooling trend. The interval of 1.74–1.54 million years ago is characterized by an insolation-dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 62 publications
8
42
0
Order By: Relevance
“…These astronomical cycles are driven by the interplay of changes in precession (19 and 23 kyr cycles caused by rotational wander in the direction that Earth's spin axis points), obliquity (41 kyr and 1.2 Myr - changes in the angle of Earth's spin axis relative to the orbital plane) and eccentricity (100 kyr, 405 kyr and 2.4 myr cycles caused by changes in the shape of Earth's orbit around the Sun) ( Berger and Loutre, 1994 ; Berger et al., 2006 ; Hays et al., 1976 ; Leuschner and Sirocko, 2003 ), and such ‘orbital forcing’ has a direct impact on monsoon ( Leuschner and Sirocko, 2003 ) and vegetation dynamics ( Claussen et al., 2006 ; Tuenter et al., 2006 ). Orbital forcing famously acted as a ‘pacemaker’ for the waxing and waning of Quaternary ice sheets ( Hays et al., 1976 ), and there is evidence of its impact on the Tibetan environment over the past 1.74 million years ( Zhao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These astronomical cycles are driven by the interplay of changes in precession (19 and 23 kyr cycles caused by rotational wander in the direction that Earth's spin axis points), obliquity (41 kyr and 1.2 Myr - changes in the angle of Earth's spin axis relative to the orbital plane) and eccentricity (100 kyr, 405 kyr and 2.4 myr cycles caused by changes in the shape of Earth's orbit around the Sun) ( Berger and Loutre, 1994 ; Berger et al., 2006 ; Hays et al., 1976 ; Leuschner and Sirocko, 2003 ), and such ‘orbital forcing’ has a direct impact on monsoon ( Leuschner and Sirocko, 2003 ) and vegetation dynamics ( Claussen et al., 2006 ; Tuenter et al., 2006 ). Orbital forcing famously acted as a ‘pacemaker’ for the waxing and waning of Quaternary ice sheets ( Hays et al., 1976 ), and there is evidence of its impact on the Tibetan environment over the past 1.74 million years ( Zhao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To help develop orbital-scale glacial history for HMA, we first examine the large-scale climate change over HMA during the last four glacial-interglacial cycles. Driven by variations in Earth's orbit and atmospheric greenhouse gases (Figures 1a and 1b), the climate model generally reproduces the temperature variability recorded in ice cores (Thompson et al, 1997) and lake sediments (Zhao et al, 2020) on the Tibetan Plateau. The modeled peak warming/cooling broadly matches with the pollen-based temperature reconstruction and δ 18 O records in ice cores (Figures 1c-1e), given the uncertainty in chronology.…”
Section: Large-scale Climate Changementioning
confidence: 57%
“…Glacier-extant and habitat area simulation. Several previous studies have shown that the climate at a millennial time scale on the eastern Tibetan Plateau is strongly impacted by monsoons, particularly the East Asian summer monsoon, which tracks changes in the westerlies and continental warming that are largely a function of mid-to high-latitude changes 55,56 . Thus, the past climate change in our study was inferred by the synthesized record of Northern Hemisphere (30°-90°N) temperature anomaly since the last deglaciation 57,58 .…”
Section: Methodsmentioning
confidence: 99%